Patisiran for the treatment of patients with p.Ile88Leu hereditary transthyretin amyloidosis: an Italian real-life experience - Urbinati, Giacomo; Cani, Ilaria; Currò Dossi, Marco; Longhi, Simone; Carigi, Samuela; Gagliardi, Christian; Biagini, Elena; Galiè, Nazzareno; Cortelli, Pietro; Guaraldi, Pietro (Frontiers in Neurology, 2024)
Objectives Evidence on the activity of patisiran therapy in specific subgroups of patients with hereditary transthyretin amyloidosis variant (ATTRv) is still scarce. This prospective real-world study was designed to provide the first in-depth clinical data on the effectiveness of patisiran in patients with ATTRv reporting the p.Ile88Leu variant, the most widespread variant in the Emilia-Romagna regional area, which has been less represented in previous clinical trials. Patients and methods This prospective study evaluated all the patients with genetically proven ATTRv (p.Ile88Leu) and polyneuropathy treated with patisiran in the Emilia-Romagna referral centers for ATTRv (Institute of Neurological Sciences in Bologna and Division of Neurology in Rimini) from March 2021 to April 2023. All subjects underwent clinical and neurological evaluations at baseline and after 9–12 months of treatment. Results A total of 22 patients were included in the study; the median age was 73 years (IQR: 9), the age at diagnosis was 72 years (IQR: 10), and the disease duration was 1.6 years (IQR: 2.3). We observed stability of all considered neurological and cardiological parameters at 9–12 months after the beginning of patisiran treatment. Conclusion Our findings support the clinical data regarding the effectiveness of patisiran in stabilizing the disease course and extend this activity to the subset of patients with the p.Ile88Leu variant.